Electrification for "Under Grid" households in Rural Kenya. (June 2016) - Lee, Kenneth; Brewer, Eric; Christiano, Carson; Meyo, Francis; Miguel, Edward; Podolsky, Matthew; Rosa, Javier; Wolfram, Catherine
Abstract: In Sub-Saharan Africa, 600 million people live without electricity. Despite ambitions of governments and donors to invest in rural electrification, decisions about how to extend electricity access are being made in the absence of rigorous evidence. In this paper, we present high-resolution spatial data on electrification rates in rural Kenya in order to quantify and visualize energy poverty in a novel way. Using our dataset of 20, 000 geo-tagged structures in Western Kenya, we provide descriptive evidence that electrification rates remain very low despite significant investments in nearby grid infrastructure. This pattern holds across time and for both poor and relatively well-off households and businesses. We argue that if governments wish to leverage existing infrastructure and economies of scale, subsidies and new approaches to financing connections are necessary.